The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.30588/jmp.v5i1.144
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Wisata Kuliner Oleh-oleh Khas Yogyakarta terhadap Perekonomian Masyarakat

Abstract: <p>Tourism industry that has recently experienced rapid development is culinary field. It is a tourism activity concerning the provision of food and beverage. The present tourists’ trend is to visit a tourism area to find or hunt local foods. Besides, they are not reluctant to pay in high price to enjoy a meal. Culinary tourism of Yogyakarta special souvenirs become DIY tourism power which is able to create great benefit to the society economy. Business of Yogyakarta special souvenirs such as bakpia, gep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…In line with the research above [8]who did a research on Dampak Wisata Kuliner Oleholeh Khas Yogyakarta terhadap Perekonomian Masyarakat 'The Impact of Yogyakarta Special Souvenirs Culinary Tourism toward social economy' found that the promotion of culinary tourism of Yogyakarta special souvenirs has positive effect on social economy in this sector. Potensi Wisata Kuliner Dalam Mendukung Pariwisata Di Kota Padang 'The Potency of Tourim Culinary in Supporting Tourism in Padang [9] found that The external environment includes opportunities and threats that will influence the use of Minang specialties in developing the potency of culinary tourism in West Sumatra.…”
Section: Introductionmentioning
confidence: 69%
“…In line with the research above [8]who did a research on Dampak Wisata Kuliner Oleholeh Khas Yogyakarta terhadap Perekonomian Masyarakat 'The Impact of Yogyakarta Special Souvenirs Culinary Tourism toward social economy' found that the promotion of culinary tourism of Yogyakarta special souvenirs has positive effect on social economy in this sector. Potensi Wisata Kuliner Dalam Mendukung Pariwisata Di Kota Padang 'The Potency of Tourim Culinary in Supporting Tourism in Padang [9] found that The external environment includes opportunities and threats that will influence the use of Minang specialties in developing the potency of culinary tourism in West Sumatra.…”
Section: Introductionmentioning
confidence: 69%
“…Another contribution from this sector is the expansion of employment opportunities for the community (Hakim, 2017;Isniati & Yusrini, 2019). This can be seen, for example, from the operation of hotels and inns, restaurants, travel businesses, souvenir shops, entertainment (event) (Darsini & Darsana, 2014;Rismiyanto & Danangdjojo, 2015;Sanaubar et al, 2017;Santoso, 2014;Setiyanti & Sadono, 2011). This means that domestic and foreign tourist visits to various tourist objects in the DKI Jakarta Province will indirectly open up job opportunities for the local people, and in turn are expected to help reduce unemployment.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © 2020 Jurnal Pariwisata Pesona Wisata kuliner juga dapat dimaksudkan sebagai wisata yang mana memberikan banyak fasilitas pelayanan dan juga aktivitas kuliner yang dibuat terpadu untuk dapat memenuhi apa yang dibutuhkan oleh wisatawan (Rismiyanto & Danangdjojo, 2015). Wisata kuliner merupakan komponen yang penting dari industri pariwisata, dan dapat memberikan pengalaman penting bagi para wisatawan yang datang berkunjung (Komaladewi et al, 2017).…”
Section: Pendahuluanunclassified